(untitled) (Global Journal of Science Frontier Research, 2020)
The aim of present study was to determine the common diseases encountered by Animal Rahat teams in working bullocks in Western Maharashtra, India and also emphasize on diseases of higher prevalence encountered in more numbers during hard working season viz. sugarcane crushing season. This is based on analysis of Animal Rahat ’Streatment data of five years which is from April, 2015 to March, 2020. Animal Rahat, an animal welfare organization provides free treatment services to working bullocks in 180 villages and 26 sugar factories of Western Maharashtra i.e. in Solapur, Sangli, Satara and Kolhapur districts. Every year’s thousands of animals are being treated for various ailments and these treatment data’s are recorded in specified treatment register and on monthly basis these treatment data’s are converted to soft and analysed.